Effects of monetary policy decisions on professional forecasters' expectations and expectations uncertainty - Sami Oinonen; Maritta Paloviita; Matti Viren (Bank of Finland, 2018)
In this paper, we examine how professional forecasters' expectations and expectation uncertainty have reacted to the ECB's interest rate decisions and non-conventional monetary policy measures during the period 1999-2017. The analysis makes use of a conventional dif-in-dif type set up with different time series tools. The results indicate that expectations have been sensitive to policy actions, but all forecasters' reactions do not seem to follow the basic predictions of a standard New Keynesian model. Also the relationship between inflation and output forecasts does not seem to follow a Phillips curve type relationship. Moreover, short- and long term reactions to policy are often weakly related and of different sign. Interestingly, subjective forecast uncertainty measures are very sensitive to policy measures. Thus, there seems to be much heterogeneity in forecasters' reactions to most policy decisions. All uncertainty measures, including long-term inflation uncertainty, have increased over time. This has to be taken into account when considering the anchoring of inflation expectations to the inflation target.
URN:NBN:fi:bof-201811202136
Keywords: E32; G02; 330